If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(5x + 8) = 8x + 18 Reorder the terms: 5x + 2(8 + 5x) = 8x + 18 5x + (8 * 2 + 5x * 2) = 8x + 18 5x + (16 + 10x) = 8x + 18 Reorder the terms: 16 + 5x + 10x = 8x + 18 Combine like terms: 5x + 10x = 15x 16 + 15x = 8x + 18 Reorder the terms: 16 + 15x = 18 + 8x Solving 16 + 15x = 18 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 16 + 15x + -8x = 18 + 8x + -8x Combine like terms: 15x + -8x = 7x 16 + 7x = 18 + 8x + -8x Combine like terms: 8x + -8x = 0 16 + 7x = 18 + 0 16 + 7x = 18 Add '-16' to each side of the equation. 16 + -16 + 7x = 18 + -16 Combine like terms: 16 + -16 = 0 0 + 7x = 18 + -16 7x = 18 + -16 Combine like terms: 18 + -16 = 2 7x = 2 Divide each side by '7'. x = 0.2857142857 Simplifying x = 0.2857142857
| 6p+-3(4p+3)+4(6p+1)=43 | | 5(m-2)=-(6m-1) | | x(x-9)(x+3)=0 | | Z-6.8=7.56 | | 0=6x+x^2-31 | | 1620x-350=680x+470 | | 1/3p-p=12 | | (8x+3)(5x+8)=180 | | 3x+9(3x+1)=9x-6 | | 6(4x+3)=138 | | 5x+9i=10-3yi | | 2x+9+9x-8=8x+19 | | 15x-3(6+5x)=-18 | | x*x=16+(x+-4)(x+2) | | 8+6y=7y | | 2x+6=-6-2 | | -4(v+7)=-(1+7v) | | 14.3=-1.4-3d | | x*x=16+(x-4)*(x+4) | | P/g=10 | | 9x-5-6x-2=6x-1 | | -10-9z+10z=-12 | | 5g+2=10-3g-8 | | -5r+5=-6r+2 | | (3x-1)(6x+9)=0 | | (x-4)*(x+4)=486 | | 3.50t+5.50+6t=51 | | d+6=10-3d | | 1-7n-1=-8n | | (x-4)*(x-4)=486 | | 60+60+x-20=360 | | 9x-5-6x-2=6x-7 |